Can cover crops improve soil ecosystem services in water‐limited environments? A review. Issue 1 (14th November 2021) - Blanco‐Canqui, Humberto; Ruis, Sabrina J.; Holman, Johnathon D.; Creech, Cody F.; Obour, Augustine K.
Abstract: Cover crops (CCs) are considered to deliver multiple soil ecosystem services, but such potential could vary by climatic region. This leads to the question: can CCs improve soil ecosystem services in low precipitation regions? To answer this, we reviewed published data up to 27 July 2021 regarding CC impacts on CC biomass production, soil organic C (SOC) accumulation, water and wind erosion, soil water, nitrate leaching potential, soil microbial biomass, weed management, crop yields, and livestock production (i.e., CCs as forage) across regions with <500 mm precipitation. Literature indicates that CCs produce 2.37 ± 2.30 Mg ha −1 of aboveground biomass, but belowground biomass data are unavailable. Cover crops increased soil wet aggregate stability (63% of CC vs. no CC comparisons), suggesting reduced water erosion potential with CCs. Also, CCs reduced nitrate leaching potential (74% of comparisons) and soil water (50%), increased soil microbial biomass (73%), and did not affect dry aggregate stability (67%) and crop yields (56%). Cover crops accumulated SOC in 59% of comparisons. Averaged across all comparisons, CCs accumulated 0.43 Mg SOC ha −1 yr −1 in the upper 30‐cm depth. This SOC accumulation rate is within the range of SOC accumulation across all regions in previous reviews. Cover crops can reduce weed biomass by 89%. Also, when hayed or grazed, CCs could provide net economic returns without negating soil benefits. Overall, CCs improve most soil ecosystem services without many detrimental effects on crop yields in water‐limited environments, although more long‐term (>10 yr) data are needed for definitive conclusions. Core Ideas: Cover crops produce 2.37 ± 2.30 Mg ha −1 of aboveground biomass in water‐limited regions Cover crops generally reduce leaching potential, suppress weeds, and improve soil biology. Cover crops accumulate soil C in about 59% of comparisons in water‐limited regions. Cover crops do not increase crop yields but may reduce yields in low precipitation years. Cover crops improve most ecosystem services in water‐limited environments.